THE CORE FUNCTIONS OF DEFINITE, INDEFINITE, AND ZERO ARTICLES - Panjiyeva N. N; Ravshanova Nafosat Ravshan kizi (TADQIQOTLAR, 2026)
This article explores the core functions of definite, indefinite, and zero articles in English grammar. It provides a comprehensive overview of how these articles are used to convey specificity, generality, and the absence of an article. The article delves into the rules governing the use of each type of article, illustrated with examples, and highlights their significance in sentence structure and meaning. Additionally, it addresses common challenges learners face when using articles and offers practical tips for mastering their use.